Temporal trends and predictors of salvage cancer treatment after failure following radical prostatectomy or radiation therapy: An analysis from the CaPSURE registry. Issue 4 (25th October 2013) - Cary, K. Clint; Paciorek, Alan; Fuldeore, Mahesh J.; Carroll, Peter R.; Cooperberg, Matthew R.
Abstract : BACKGROUND: Prostate cancer treatment after failure of primary therapy by either radical prostatectomy or radiation therapy can vary greatly. This study sought to determine trends and predictors of salvage treatment after failure of primary treatment in a community cohort over the past 10 years. METHODS: From the community‐based Cancer of the Prostate Strategic Urologic Research Endeavor (CaPSURE) database, 6275 patients were identified who initiated a form of primary treatment for prostate cancer; 839 of these were identified as failing treatment by biochemical recurrence or initiation of secondary treatment between 2000 and 2010. Salvage therapy was categorized as either systemic, local, or none. Patient characteristics were tested for association with salvage therapy using analysis of variance, Pearson chi‐square tests, and multinomial logistic regression analysis. RESULTS: Of the 839 patients identified as failing therapy, 390 (47%), 146 (17%), and 303 (36%) received systemic, local, or no salvage therapy, respectively. Type of primary treatment received was associated with type of salvage therapy ( P < .01). There has been an increasing trend in the use of local salvage therapy over the past 10 years ( P = .04). Primary treatment type and biopsy Gleason score were significantly associated with type of salvage therapy. CONCLUSIONS: The use of local salvage therapy has increased over the past decade, whereas the use of systemic salvage therapy has declined. Primary treatment is an important factor in determining which type of salvage therapy a patient will receive. Cancer 2014;120:507–512 . © 2013 American Cancer Society . Abstract : There is an increasing trend in the utilization of local salvage therapy in prostate cancer patients over the past decade. The type of primary prostate cancer treatment and biopsy Gleason score are most predictive of type of salvage therapy.